To knit the knot: embodied mind in John Donne's "The Ecstasy". Issue 4 (8th August 2019) - Helms, Nicholas R.
ABSTRACT: For John Donne's "The Ecstasy", cognitive ecology offers a new approach to the divide between Platonism and Aristotelianism in the poem, presenting a continuum between body and soul rather than an opposition or equivalence. In this essay, I argue that Donne charts a continuum of body and soul through a chain of metaphors, knitting together an ecstasy that is both outside and beside the self. One can neither conceive of nor experience such an ecstasy without employing embodied metaphors, metaphors that enable the conceptual movement within the poem. Strictly speaking, souls cannot move, speak, mix, or descend: all these actions are embodied concepts that use human motor-schema to map out abstract notions. The soul's movement occurs in a conceptual space carved out through this chaotic change and exchange of embodied metaphors. This movement of the soul through the body, via the body, knits the "knot, which makes us man".